Upgrade [videorecording (DVD)] - Whannell, Leigh, 1977-; Marshall-Green, Logan, 1976-; Gabriel, Betty; Gilbertson, Harrison (Universal Pictures Home Entertainment, 2018)
Grey Trace and his wife suffer a brutal mugging which leaves him paralyzed and results in her murder. After the horrific crime, a special new technology is brought to him with a chip implanted in his spine called Stem. With that chip, he now has a new upgraded control over his body and abilities. Set in the near-future, Grey embarks on an exhilarating quest to gain revenge by using his new skills.